Public acceptance of residential solar photovoltaic technology in Malaysia - Ahmad, Salman; Razman, Mat Tahar; Cheng, Jack Kie; Yao, Liu (Emerald Publishing Limited, 2017)
Purpose : Gaining independence from fossil fuels and combating climate change are the main factors to increase the generation of electricity from renewable fuels. Amongst the renewable technologies, solar photovoltaic (PV) is believed to have the largest potential. However, the number of people adopting solar PV technologies is still relatively low. Therefore, the purpose of this paper is to examine the household consumers’ acceptance of solar PV technology being installed on their premises. Design/methodology/approach : To examine the solar PV technology acceptance, this study uses technology acceptance model (TAM) as a reference framework. A survey was conducted to gather data and to validate the research model. Out of 780 questionnaires distributed across Malaysia, 663 were returned and validated. Findings : The analysis revealed that perceived ease of use, perceived usefulness and attitude to use significantly influenced behavioural intention to use solar PV technology. Research limitations/implications : This study contributes by extending the understanding of public inclination towards the adoption of solar PV technology. Also, this study contributes in identifying the areas which need to be examined further. However, collecting data from urban peninsular Malaysian respondents only limits the generalization of the results. Practical implications : On the policy front, this study reveals that governmental support is needed to trigger PV acceptance. Originality/value : This paper uses TAM to analyse the uptake of solar PV technology in Malaysian context.